Retention Strategies in Public and Private Schools: A Comparative Analysis - Mbena, Atujisyaghe L.; Swai, Idda Lyatangoa (Journal of Policy and Leadership, 2024)
While teacher retention is necessary in schools, it can only be achieved with proper strategies. The study examined the teachers' retention strategies in public and private Secondary Schools in Morogoro Municipal Council. The study adopted a qualitative approach with a case study design. A purposive sampling technique was employed to select 26 participants. Interviews, documentary reviews and observations were used to collect data. The data were analysed using thematic and content analysis and presented using direct quotations and narrations. The findings found that public and private secondary schools use various teacher retention strategies, including job security, engagement in decision-making, good working environment, good working relationship, good salary, allowances, rewards and recognition. The approach that retains teachers in public schools varies from those that maintain teachers in private schools. Most public-school teachers seem highly satisfied with job security, the salary they receive on time, and their involvement in decision-making and working relationships. In contrast, teachers in private schools feel happy with the recognition, appreciation, and extra pay based on student performance. They are also highly dissatisfied with their salaries, which are low and always received late; they are not involved in decision-making and need more job security. Teachers expressed their fears about working on short-term contracts, and thus, they wish to move to public schools if they secure an opportunity. The study recommends that schools should learn from each other on the best practices for retaining teachers.